Cores & bands. Graphic discourses on the open floor plan (ARQUISUR Revista, 2024)
This article reflects on the graphic representation of collective housing projects based on the concept of an open plan. This reflection is addressed by exploring different conceptualizations developed by some authors who have theorized about housing flexibility. These authors draw a distinction between two strategies for organizing an open plan: concentrating service spaces in nuclei or structuring them through linear bands. These strategies are illustrated by a selection of projects and works carried out in Europe between the mid 80s and the late 90s. These are well-known projects that have been widely disseminated in the literature and have influenced other projects, both in the professional field and in academic training. The study of the selected cases focuses on the expressive resources used in draw-ing the plans, since this is the most appropriate representation for communicating the uses of space. A comparative analysis of the examples leads to the conclusion that some resources are transversal and can be extrapolated to other cases, and thus allow for the development of a graphic discourse on housing flexibility.
Keywords: graphic discourse; flexibility; floor plan; representation; collective housing